2018
DOI: 10.1016/j.jad.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal maternal depression, antidepressant use and infant sleep outcomes: Exploring cross-lagged associations in a pregnancy cohort study

Abstract: Maternal depression and antidepressant use were not found to be significant factors in infant sleep problems and, likewise, infant sleep problems were not associated with maternal depression. However, postpartum maternal cognitions around six months postpartum regarding limit-setting at night may predict increases in later nocturnal infant signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The bidirectional models between maternal depression symptoms and infant Bedtime Problems, Positive Sleep Habits, Daytime Sleepiness and Total Sleep Problems presented a poor fit, which may suggest that the links between maternal depression symptoms and these specific sleep problems are mainly unidirectional during the first 6 months. Considering that the Bedtime Problems subscale assesses infant frequent night awakening, these results are congruent with previous findings that found no bidirectional links between maternal postpartum depression symptoms and infant night awakenings (Galbally et al., 2018). However, a previous study with older children revealed reciprocal links between maternal mood and children’s sleep problems, although not considering the effects of maternal prenatal depression symptoms (Bell & Belsky, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The bidirectional models between maternal depression symptoms and infant Bedtime Problems, Positive Sleep Habits, Daytime Sleepiness and Total Sleep Problems presented a poor fit, which may suggest that the links between maternal depression symptoms and these specific sleep problems are mainly unidirectional during the first 6 months. Considering that the Bedtime Problems subscale assesses infant frequent night awakening, these results are congruent with previous findings that found no bidirectional links between maternal postpartum depression symptoms and infant night awakenings (Galbally et al., 2018). However, a previous study with older children revealed reciprocal links between maternal mood and children’s sleep problems, although not considering the effects of maternal prenatal depression symptoms (Bell & Belsky, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…According to the transactional model (Sadeh, Tikotzky, & Scher, 2010; Sameroff, 1993), bidirectional links may also occur – maternal depression may influence and concurrently be influenced by infant sleep problems. Although the effects of maternal depression symptoms on infant sleep problems (Bat‐Pitault et al., 2017; Martini et al., 2017) and the effects of infant sleep problems on maternal depression symptoms (Wake et al., 2006) have been separately examined in the literature, the bidirectional links were more recently investigated (Galbally, Watson, Teti, & Lewis, 2018; Ystrom, Hysing, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, trying to respond to a crying infant immediately every time might put mothers under a lot of stress, increase fatigue (Barr et al, 2014; Long et al, 2018) and may increase depression (Petzoldt, 2018). Moreover, mothers' own expectations of responding to their crying infants immediately might even increase later infant night waking (Galbally, Watson, Teti, & Lewis, 2018). For infants' healthy development, the importance of maternal self‐care and good maternal mental health is invaluable (Kurth, Kennedy, Spichiger, Hosli, & Stutz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies on sleep in infants of depressed pregnant women demonstrate significant changes. In a study comparing infants born to depressed and control women, maternal prenatal depression and antidepressant use were not significant predictors of infant sleep problems, as reported by the mother, in 6- and 12-month-old infants (Galbally et al, 2018).…”
mentioning
confidence: 93%